The analysis critical thinking skills of guidance and counseling students : A pilot study using RASCH model analysis - Marfu'i, Lucky Nindi Riandika Lucky (Konselor, 2019)
This study identified the critical thinking skills of Guidance and Counseling students. The analysis of this capability was illustrated in the scalogram resulted from the RASCH model analysis. The respondents were Guidance and Counseling students at a public University, in Bandung, Indonesia. The data obtained was used as a pilot study in measuring the critical thinking skill test constructed by the author. The results showed that the students' critical thinking skills were in the low category, with a percentage of 44%. The scalogram picture showed that there were three students who gave inconsistent patterns for several questions which showed that the result was still valid. The result of this study could be a reference for giving group counseling to some students who had inconsistent response patterns. In conclusion, counseling with a cognitive approach needed to be held in improving the critical thinking skills of Guidance and Counseling students who had low levels of critical thinking skill as a follow-up to this research. The implication of this study was that the research data could be used as a reference in the preparation of the guidance and counseling service program related to critical thinking skills.